STUDI KOMPARATIF DELIK PENISTAAN AGAMA DALAM PERSPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Izwany, Bonita; Firdaus, Firdaus (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2022)
This study aims to explain the sanctions for religious blasphemy according to Islamic law and positive law. Indonesia is a country that guarantees freedom of religion for everyone as stated in Article 28 letter E of the 1945 Constitution of the Republic of Indonesia. In this case, the Qur'an prohibits everyone from insulting other people's religions, as contained in surah al-An'am verse 108. So this writing can provide an explanation of the sanctions for blasphemy in Islam and positive law. The results of the research show that the offense of blasphemy in jinayah fiqh has clearer legal regulations and stricter sanctions. Meanwhile, the offense of religious blasphemy in the Criminal Code has an unclear formulation and sanctions that do not have a deterrent effect on perpetrators of religious blasphemy. Jumhur Ulama agrees that if the perpetrator is a Muslim or infidel, then the law for that person is apostasy and is punishable by death. However, Ulama differ in their opinions regarding the law imposed if the perpetrator is a dhimmi infidel.